2016
DOI: 10.1016/j.oregeorev.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characteristics of biotite from felsic intrusive rocks around the Sisson Brook W–Mo–Cu deposit, west-central New Brunswick: An indicator of halogen and oxygen fugacity of magmatic systems

Abstract: The Sisson Brook W-Mo-Cu deposit was formed by hydrothermal fluids likely related to the Nashwaak Granites (muscovite-biotite granite, Group I; and biotite granite, Group II) and related dykes (biotite granitic dykes, Group III, and a feldspar-biotitequartz porphyry dyke, Group IV). Chemical data obtained using EPMA and LA-ICP-MS data of primary magmatic biotites were used to investigate magmatic processes and associated hydrothermal fluids. Trace element features of biotite in Group I two-mica granite suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…Lu et al [14] suggested that the fertile magmas commonly contain high (Ce/Nd)/Y and high Eu N /Eu N * ratios. However, Eu N /Eu N * of zircon grain is also dependent on the magma oxidation state [5,31,40,46]. In this study, the lack of positive Ce N /Ce N * vs. Eu N /Eu N * correlation, and the presence of positive Eu N /Eu N * vs. (Ce/Nd)/Y correlation suggest that Eu N /Eu N * is probably affected by water content (Figures 6c and 7a).…”
Section: Magma Water Contentmentioning
confidence: 49%
See 1 more Smart Citation
“…Lu et al [14] suggested that the fertile magmas commonly contain high (Ce/Nd)/Y and high Eu N /Eu N * ratios. However, Eu N /Eu N * of zircon grain is also dependent on the magma oxidation state [5,31,40,46]. In this study, the lack of positive Ce N /Ce N * vs. Eu N /Eu N * correlation, and the presence of positive Eu N /Eu N * vs. (Ce/Nd)/Y correlation suggest that Eu N /Eu N * is probably affected by water content (Figures 6c and 7a).…”
Section: Magma Water Contentmentioning
confidence: 49%
“…It was interpreted that "wet" magmas can suppress early plagioclase crystallization, which causes the low Dy/Yb and high Eu N /Eu N * ratios. However, the Eu N /Eu N * ratios in zircon not only vary with water content but also with the redox state [14,34,[45][46][47]. Hence, in this study, (Ce/Nd)/Y and Eu N /Eu N * ratios are both selected as proxies for the water content of magma.…”
Section: Water Content Estimationmentioning
confidence: 99%
“…Based on analysis of the composition of the different types and stages of biotite and apatite, we can invert the changes in the physical and chemical conditions, such as the temperature, oxygen fugacity, and halogen fugacity, in the magmatic and hydrothermal stages (Bao et al, ; Jin et al, ; Li et al, ; Mao et al, ; Parsapoor et al, ; Smith, ; Xiao et al, ; Xing et al, ; Yuan et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Biotite and apatite are common minerals in magmatic rocks, both of which can form during either magmatic or hydrothermal processes. By using the chemical composition of different genetic types of biotite, the changes in the physical and chemical conditions in the magmatic‐hydrothermal system during the mineralization of porphyry deposits can be revealed (e.g., Bao, Webster, Zhang, Goldoff, & Zhang, ; Jin, Gao, Chen, & Zhao, ; Mao, Zhong, Zhu, Lin, & Zhao, ; Parsapoor, Khalili, Tepley, & Maghami, ; Xiao et al, ; Xing, Shu, Zhao, & Xu, ; Zhang, Lentz, Thorne, & McFarlane, ). In addition, by using the chemical composition of different genetic types of apatite, the hydrothermal interaction mechanisms in the mineralization of the Kiruna‐type and iron oxide‐(Cu–Au) deposit style (IOCG) deposits can be constrained (e.g., Bonyadi, Davidson, Mehrabi, Meffre, & Ghazban, ; Harlov et al, ; Heidarian, Lentz, Alirezaei, McFarlane, & Peighambari, ; Krneta, Ciobanu, Cook, Ehrig, & Kontonikas‐Charos, ; Taghipour, Kananian, Harlov, & Oberhänsli, ; Torab & Lehmann, ; Zeng, Zhao, Li, Hu, & McFarlane, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our knowledge of the HF, HCl, and H 2 O fugacity of hydrothermal fluids associated with porphyry Cu mineralization and hydrothermal alteration is based on limited published thermodynamic data (Parry and Jacobs, 1975;Parry et al, 1978;Munoz and Swenson, 1981;Munoz, 1984;Loferski and Ayuso, 1995). Presently, there are several studies dealing with mineral chemistry of hydrothermal biotite from numerous porphyry copper deposits worldwide, such as Kahang deposit, Iran (Afshooni et al, 2013), Lar deposit, Iran (Moradi et al, 2016), Dexing deposit, China (Bao et al, 2016), and Sisson Brook deposit, New Brunswick, Canada (Zhang et al, 2016). Halogen chemistry of magmatic biotite within the mineralization-bearing tonalite porphyry in Batu Hijau deposit, Indonesia, was described by Idrus et al (2007).…”
Section: Introductionmentioning
confidence: 99%